Proceedings of the 7th International Conference on English Language and Teaching (ICOELT 2019) 2020
DOI: 10.2991/assehr.k.200306.034
|View full text |Cite
|
Sign up to set email alerts
|

Listening Comprehension and Listening Anxiety: A Case of Basic Listening Class Students at English Department UNP Padang

Abstract: Listening anxiety which makes someone feel tensions, fear, uncomfortable and worry was suspected to affect students' comprehension in listening class. Therefore, this research aims to find the relationship between listening anxiety and listening comprehension of English department students who had taken Basic Listening class at Universitas Negeri Padang. The type of research used in this research was quantitative research. The population of this research was the second year students in Basic Listening Class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…LCA is the fear of misunderstanding, incapacity, or inability to react psychologically to other people's communications (Wheeless 1975). According to Adnan et al (2020), LCA "blocks the students from achieving the best comprehension they can get in listening" (p. 201). Adnan et al emphasized that students with higher LCA have lower listening comprehension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA is the fear of misunderstanding, incapacity, or inability to react psychologically to other people's communications (Wheeless 1975). According to Adnan et al (2020), LCA "blocks the students from achieving the best comprehension they can get in listening" (p. 201). Adnan et al emphasized that students with higher LCA have lower listening comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to LCA, some English major students have problems comprehending a listening record. For example, Adnan et al (2020) conducted a study on 30 English major students at the University of Negeri Padang in Indonesia to find out the relationship between listening anxiety and listening comprehension. The result of the study revealed that there is a negative correlation between listening anxiety and listening comprehension indicating that students with higher listening anxiety have lower listening comprehension.…”
Section: Introductionmentioning
confidence: 99%